Cost-Effectiveness of Bariatric Surgery versus Medication Therapy for Obese Patients with Type 2 Diabetes in China: A Markov Analysis. (20th December 2019) - Wan, Bin; Fang, Nan; Guan, Wei; Ding, Haixia; Wang, Ying; Ge, Xin; Liang, Hui; Li, Xin; Zhan, Yiyang
Abstract : Aims/Introduction . The present study estimated the cost-effectiveness of bariatric surgery versus medication therapy for the management of recently diagnosed type 2 diabetes mellitus (T2DM) in obese patients from a Chinese health insurance payer perspective. Materials and Methods . A Markov model was established to compare the 40-year time costs and quality-adjusted life-years (QALYs) between bariatric surgery and medication therapy. The health-care costs in the bariatric surgery group, proportion of patients in each group with remission of diabetes, and state transition probabilities were calculated based on observed resource utilization from the hospital information system (HIS). The corresponding costs in the medication therapy group were derived from the medical insurance database. QALYs were estimated from previous literature. Costs and outcomes were discounted 5% annually. Results . In the base case analysis, bariatric surgery was more effective and less costly than medication therapy. Over a 40-year time horizon, the mean discounted costs were 86, 366.55 RMB per surgical therapy patient and 113, 235.94 CNY per medication therapy patient. The surgical and medication therapy patients lived 13.46 and 10.95 discounted QALYs, respectively. Bariatric surgery was associated with a mean health-care savings of 26, 869.39 CNY and 2.51 additional QALYs per patient compared to medication therapy. Uncertainty around the parameter values was tested comprehensively in sensitivity analyses, and the results were robust. Conclusions . Bariatric surgery is a dominant intervention over a 40-year time horizon, which leads to significant cost savings to the health insurance payer and increases in health benefits for the management of recently diagnosed T2DM in obese patients in China.